KEWENANGAN PEMERIKSAAN BADAN PEMERIKSA KEUANGAN ATAS BADAN USAHA MILIK NEGARA - Anggoro, Cahyo (Varia Justicia, 2018)
Audit Board of Indonesia (BPK) performs audits on the management and accountability of state finances, including those implemented by State Owned Enterprises (SOE). This study aims to see the synchronization of various regulations related to the authority of BPK in conducting SOE audit, as well as audit practices conducted by BPK on SOEs in the period of 20012-2017. This research is conducted by using normative legal research method. Data collection is done through library research by perform a search regulations, scientific books, and other data relevant to the study. Based on the results of the analysis it is known that first, the Acts regulating the state finance, state financial audit, BPK and SOE have been in sync with each other related to the BPK audit of SOEs. BPK audit of SOEs is the authority of BPK's attribution derived from the 1945 Constitution and further regulated in Acts. Second, the implementation of BUMN audits by BPK period 2012-2017 is conduct with three types of audit, namely financial audit, performance audit and  a specific purpose audit on state-owned companies in the form of Persero and Perum.